Transcutaneous vagus nerve stimulation does not affect attention to fearful faces in high worriers. (February 2019) - Verkuil, Bart; Burger, Andreas M.
Abstract: People suffering from chronic worries pay excessive attention to emotional information. In this study we examined whether a reduced ability to inhibit attention from fearful faces (i.e. inhibition of return; IOR) can be attributed to the low vagus nerve activity observed in high worriers. Our pre-registered hypothesis was that transcutaneous auricular vagus nerve stimulation (tVNS) would enhance IOR to fearful faces. Ninety-four students who scored above a pre-determined cut-off on the Penn State Worry Questionnaire were randomly allocated to receive either tVNS (n = 45) or sham stimulation of the earlobe (n = 49). Meanwhile, to assess IOR, they performed an emotional exogenous cueing task wherein neutral and fearful faces predicted the target location at chance level. Resting levels of HRV were also collected before stimulation onset. Results showed that levels of trait worry were associated with reduced IOR, but resting levels of HRV were not. Critically, tVNS did not affect performance on the exogenous cueing task when compared to sham stimulation. These findings did not confirm the hypothesized causal role of vagus nerve activity in maintaining disrupted IOR for emotional information. They also provide evidence that high levels of worry are associated with generally reduced IOR. This points to a clear need to understand the neurobiological basis of inhibitory problems in worriers. Highlights: Sham-controlled experiment in selected worriers performing a spatial cueing task. Tested if stimulating the vagus promotes attentional disengagement to fearful faces. Transcutaneous stimulation of the vagus nerve did not affect task performance. Higher levels of worrying were related to prolonged attention to distracting cues.